Studies on the sulphation of 3,4-dihydroxyphenylethylamine (dopamine) and related compounds by rat tissues - Jenner, William N. (1973)
The formation of sulpho-conjugates of 3,4-dihydroxyphenylethylamine (dopamine) and related compounds was examined in preparations of rat tissues. Liver high-speed-supernatant preparations readily transferred sulphate from adenosine 3′-phosphate 5′-sulphato-phosphate to dopamine under standard conditions. The main product was identified as the 3-O-sulphate. The preparation also sulphated the 3- and 4-methoxy derivatives but to a lesser extent (44% and 95% respectively) relative to dopamine. Brain preparations possessed only half the activity of liver but formed both the 3- and 4-O-sulphates in the molar ratio of 1.7:1. l-3,4-Dihydroxyphenylalanine (l-dopa) in both tissue preparations did not yield any significant amount of sulpho-conjugate when the dopa decarboxylase present was inhibited. The sulphotransferase activity of preparations was doubled in the presence of dithiothreitol and it was concluded that l-tyrosine methyl ester sulphotransferase was the enzyme involved. A method for the preparation of authentic dopamine 3-O-sulphate and 4-O-sulphate was developed.